Implementation of Winnowing Algorithm and Simple Additive Weighting SAW for Publication Reference Journal Search System - Imam Fakhruddin; Indra Gita Anugrah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
Reference journals have several different writing arrangements. In the reference journal, there is some information or words needed in making scientific journals. With this information or word retrieval system, it can help to find journals that match the similarities between input and information or words in the journal that will be used as a reference. In this study, the input process of equations and information or words will be processed using the Winnowing algorithm as an algorithm that can find the similarity of words or texts with N-gram functions, rolling hash, and Jaccard Coefficient. In general, the search only uses the same words or text without any weighting on the composition of the reference journal. To be able to find journals and their level of importance in the order of journals, a weighting method is needed. This study also uses the Simple Additive Weighting (SAW) method as a process to determine the value of the order of urgency in journals so that it can provide results in the form of rankings based on searches and urgency weights in reference journals. The results of the similarity query with documents obtained 60% precision, 77% recall, and 81% accuracy, documents, and documents had 41% precision, 83% recall, and 66% accuracy. using Winnowing Algorithm, the search system can detect the similarity of text.